Development of a Canva-Based Mathematics E-Module to Facilitate Seventh Grade Students' Mathematical Problem Solving Skills in Algebraic Expressions - Nabil Maulana Yuspelto; Reni Wahyuni; Lilis Marina Angraini; Putri Wahyuni (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study was motivated by students' low mathematical problem-solving skills and the suboptimal use of technology-based learning media in mathematics instruction. In addition, the learning materials currently used are still dominated by printed textbooks, which are less engaging and have not adequately supported students' independent learning. This study aims to develop a Canva-based mathematics e-module that is valid and practical for facilitating the mathematical problem-solving skills of seventh-grade students on the topic of algebraic expressions. This research employed a Research and Development (R&D) approach using the Borg and Gall model as adapted by Sugiyono. Although the original model consists of ten stages, it was simplified into seven stages: identifying potential and problems, data collection, product design, product validation, design revision, product testing, and final product development. The research participants included two expert validators, one seventh-grade mathematics teacher, and six seventh-grade students who participated in a small-group trial. The research instruments consisted of e-module validation sheets, student worksheet (LKPD) validation sheets, a teacher response questionnaire, and a student response questionnaire. Data were analyzed using descriptive quantitative analysis by calculating the percentage of product validity and practicality. The results indicated that the Canva-based mathematics e-module achieved an average validity score of 92.34%, categorized as valid, while the accompanying student worksheets (LKPD) obtained an average validity score of 83.75%, also categorized as valid. The practicality test showed that the teacher response reached 86.1%, categorized as highly practical, whereas the students' response reached 79.16%, also categorized as highly practical. Based on these findings, it can be concluded that the Canva-based mathematics e-module on algebraic expressions meets the criteria of validity and high practicality, making it suitable for use as a learning medium to facilitate the mathematical problem-solving skills of seventh-grade junior high school students.